Fungsi Afektif Keluarga berhubungan dengan Perilaku Manajemen Perawatan Diri pada Lansia dengan Hipertensi - Irwina Angelia Silvanasari; Nurul Maurida; Trisna Vitaliati; Achmad Ali Basri (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2024)
Introduction: Self-care management is needed to improve the quality of life of elderly people with hypertension, however, the self-care management behavior displayed by elderly people with hypertension tends to be poor. The family is an important figure to take into account in fulfilling optimal self-care management for hypertensive elderly people. Objectives: This research aims to analyze the relationship between family affective function and self-care management behavior of elderly people with hypertension. Methods:  This research used a cross-sectional design with a sample of 150 respondents taken using simple random sampling. Data were analyzed using the gamma correlation test.  Results:  There is a relationship between family affective function and self-care management behavior in elderly people with hypertension with p-value = 0.000 ≤ 0.05. Discussion: Good family affective function tends to increase hypertension self-care management behavior. Elderly people with hypertension should always maintain maximum self-care management behavior. Families should maintain closeness to elderly people who suffer from hypertension in their family. Families should always respond well to the existing needs of elderly people with hypertension in their families.